Does Personality Have a Different Impact on Self-Rated Distraction, Job Satisfaction, and Job Performance in Different Office Types? - Seddigh, Aram; Berntson, Erik; Platts, Loretta G.; Westerlund, Hugo (PLOS ONE, 2016)
This study investigates the joint effect of office type (cell, shared room, open-plan, and flex) and personality, measured by the Big Five personality traits, on self-rated measures of distraction, job satisfaction, and job performance (measured by professional efficacy). Regression analyses with interactions between personality and office type were conducted on 1205 participants working in 5 organizations from both the private and public sectors. While few interactions were observed in the cases of professional efficacy and job satisfaction, several were observed between personality traits and office type on the level of distraction reported. Specifically, more emotionally stable participants reported lower distraction, particularly those working in flex offices. Both agreeableness and openness to experience were associated with higher levels of distraction among participants in open-plan compared to cell offices.